Inhaled treprostinil and forced vital capacity in patients with interstitial lung disease and associated pulmonary hypertension: a post-hoc analysis of the INCREASE study. Issue 11 (November 2021) - Nathan, Steven D; Waxman, Aaron; Rajagopal, Sudarshan; Case, Amy; Johri, Shilpa; DuBrock, Hilary; De La Zerda, David J; Sahay, Sandeep; King, Christopher; Melendres-Groves, Lana; Smith, Peter; Shen, Eric; et al.
Summary: Background: INCREASE was a randomised, placebo-controlled, phase 3 trial that evaluated inhaled treprostinil in patients with interstitial lung disease (ILD) and associated pulmonary hypertension. Treprostinil improved exercise capacity from baseline to week 16, assessed with the use of a 6-min walk test, compared with placebo. Improvements in forced vital capacity (FVC) were also reported. The aim of this post-hoc analysis was to further characterise the effects of inhaled treprostinil on FVC in the overall study population and in various subgroups of interest. Methods: In this post-hoc analysis, we evaluated FVC changes in the overall study population and in various subgroups defined by cause of disease or baseline clinical parameters. The study population included patients aged 18 years and older who had a diagnosis of ILD based on evidence of diffuse parenchymal lung disease on chest CT done within 6 months before random assignment (not centrally adjudicated). All analyses were done on the intention-to-treat population, defined as individuals who were randomly assigned and received at least one dose of study drug. The INCREASE study is registered with ClinicalTrials.gov, NCT02630316 . Findings: Between Feb 3, 2017, and Aug 30, 2019, 326 patients were enrolled in the INCREASE trial. Inhaled treprostinil was associated with a placebo-corrected least squares mean improvement in FVC of 28·5 mL (SE 30·1; 95% CI −30·8 to 87·7; p=0·35) at week 8 and 44·4 mL (35·4; −25·2 to 114·0; p=0·21) at week 16, with associated percentage of predicted FVC improvements of 1·8% (0·7; 0·4 to 3·2; p=0·014) and 1·8% (0·8; 0·2 to 3·4; p=0·028). Subgroup analysis of patients with idiopathic interstitial pneumonia showed FVC differences of 46·5 mL (SE 39·9; 95% CI −32·5 to 125·5; p=0·25) at week 8 and 108·2 mL (46·9; 15·3 to 201·1; p=0·023) at week 16. Analysis of patients with idiopathic pulmonary fibrosis showed FVC differences of 84·5 mL (52·7; −20·4 to 189·5; p=0·11) at week 8 and 168·5 mL (64·5; 40·1 to 297·0; p=0·011) at week 16. The most frequent adverse events included cough, headache, dyspnoea, dizziness, nausea, fatigue, and diarrhoea. Interpretation: In patients with ILD and associated pulmonary hypertension, inhaled treprostinil was associated with improvements in FVC versus placebo at 16 weeks. This difference was most evident in patients with idiopathic interstitial pneumonia, particularly idiopathic pulmonary fibrosis. Inhaled treprostinil appears to be a promising therapy for idiopathic pulmonary fibrosis that warrants further investigation in a prospective, randomised, placebo-controlled study. Funding: United Therapeutics Corporation.